Banking market consolidation in Asia: Evidence from acquirers, targets, and rivals - Sascha Kolaric; Florian Kiesel; Dirk Schiereck (International Journal of Finance & Economics, 2024)
We analyse the financial sector consolidation in Asia by using a comprehensive sample of bank M&As from 1995 to 2021. Our results show that M&A announcements by Asian domestic acquirers are associated with significant positive stock price returns to both acquirers and their rivals. In contrast, cross-border acquirers and their rivals experience negative but insignificant returns, while targets and their rivals record gains, regardless whether it is a domestic or cross-border transaction. Further analyses reveal that domestic acquirers obtaining larger relative increases in their market share benefit the most, indicating that market power considerations are the primary driver behind acquirers' positive returns. For cross-border acquirers, neither cultural differences nor regulatory arbitrage considerations can explain return patterns surrounding M&A announcements.
Keywords: 330; Banks; Emerging markets; Market consolidation; Market power; mergers and acquisitions (M&As); Rival market reactions